Trastuzumab: unusual responses and toxicities. (August 2009) - Ahamed, Eliyaz; Mauri, Francesco A; Pakter, Grant; Lim, Adrian; Stebbing, Justin
Trastuzumab has become the standard of care in the management of human epidermal growth factor receptor 2 (HER2)-overexpressing breast cancers, both in the metastatic and adjuvant setting. Emerging data show continued efficacy of the drug even after disease progression in combination with chemotherapy. While cardiotoxicity is well recognized with trastuzumab, unusual pulmonary toxicities are becoming apparent. Cases that reflect the unusual efficacy and unusual toxicity of trastuzumab are reported.